Beautiful Blossoms / Irinna Ibrahim - Irinna, Ibrahim (2020)
Beautiful Blossoms is a flower shop which is sole proprietorship owned by Irinna. This business is offers fresh floral arrangements with the wide selections of unique flowers and greens. There are plenty options of products and services being offered by this business, for example, mix of flower (bouquet), green and flowering house plants (house decoration), gift and baskets, and floral decoration for large events. Target market for this business is businessmen, housewives, and the elderly. Businessmen have stable income and look for an upper scale gifts for their significantothers or family/friends. In order to market these products, technology will be used by Beautiful Blossoms to market its product. Updated information on the availability of products, prices and sample designs will be made available on the media social such as Facebook, Instagram and etc. This business will get a lot of fun when it comes to special days like teacher's day, Mother’s Day, wedding anniversary, and so on. In addition, the profitability for this business is quite good, where the cash inflow is more than cash outflow. This means that, Beautiful Blossoms gains more profit.